UTERINE PROLAPSE: CAUSES AND TREATMENT TACTICS - Ubaydullayeva Shinar Azimbayevna; Axtamova Nilufar Akbarjanovna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Uterine prolapse, a subtype of pelvic organ prolapse, involves the descent of the uterus into the vaginal canal due to weakened pelvic supportive structures. This review synthesizes evidence from clinical guidelines and studies on its etiology, epidemiology, symptoms, diagnostic approaches, and management strategies. Key risk factors include vaginal childbirth, menopause, obesity, and chronic intra-abdominal pressure. Prevalence affects 41-50% of women on physical exam, but symptomatic cases are lower at around 3%, with progression risks higher in older or severe baseline cases. Conservative treatments like pelvic floor exercises and pessaries are first-line for mild to moderate prolapse, while surgical options such as hysterectomy or sacrocolpopexy offer high efficacy for severe cases. Outcomes are generally favorable, with recurrence rates of 10-30%, emphasizing the need for individualized care and preventive measures. Recommendations focus on interprofessional management to optimize patient quality of life.